Maternal plasma lipid profile and risk of spontaneous preterm labor study in a sample of Iranian women in 2019 - Zohreh Aghaei; Sepideh Hajian; Soodabeh Darvish (Iranian Journal of Nursing and Midwifery Research, 2023)
Background: Neonatal problems and adverse outcomes may be minimized by up to 90–75% when preterm delivery is diagnosed early and managed properly. This study aimed to determine the association of maternal plasma lipid indices with the occurrence of spontaneous preterm labor. Material and Methods: This matched pair case–control study was performed on 80 pregnant women referred to a teaching hospital in Tehran for childbirth in 2019. The lipid profile was assessed in women with spontaneous preterm labor and term birth. According to age, Body Mass Index (BMI), pregnancy number, employment status, and educational level, the women in each group were paired. Data were analyzed using an independent-samples t-test, Mann–Whitney U-test, Chi-square, linear regression, and conditional logistic regression. Results: Mean serum levels of total cholesterol, triglycerides, and low-density lipoprotein were all significantly higher in the case group compared with the control group (p < 0.05). The conditional logistic regression test confirmed that this association remained significant even after adjusting the effect of potentially confounding factors such as maternal age and body mass index. In addition, in linear regression the increased levels of triglyceride, total cholesterol, and low-density lipoprotein were found to be associated with 3.33-fold (1.32.–5.32 95% CI, P < 0.001), 2.94-fold (1.60–3.14 95% CI, P = 0.002), and 2.46-fold (1.31.–2.91 95% CI, P = 0.006) increased risk of preterm labor, respectively. Conclusions: High triglyceride, total cholesterol, and low-density lipoprotein serum levels may be linked to an increased chance of spontaneous preterm labor, which might be considered a risk factor for this pregnancy problem.